An intelligent based healthcare security monitoring schemes for detection of node replication attack in wireless sensor networks. (1st January 2021) - Anitha, S.; Jayanthi, P.; Chandrasekaran, V.
Highlights: Detection of replica node attack in Health Monitoring System using WSNs. Various state-of-the-art works in continuous monitoring of health are discussed. Architecture and components of healthcare monitoring system in WBAN is explained. Both TRM simulator and real-time experiments (MoteView software) are conducted. The performance of three proposed effective security mechanisms are compared. Abstract: Due to the increased growth of elderly people in recent years, healthcare systems face many challenges on the money spent for those people. Both quality and affordability has to be provided by the new technology which is the today's need. When applying WSN technologies, the advantages such as continuous monitoring with alert mechanisms and relative information are to be satisfied. Among the other challenges, due to the deployed environment, security is a key challenge. As gateway connects to the wireless networks, it is the target area for many adversaries to launch various attacks. Initially, attacker launches node compromise attack which leads to node replication attack. The introduced security methods for intelligent healthcare monitoring system effectively detect replication attack and provide protection to the system. The potential application of proposed methods namely Exponential Moving Average based Replica Detection (EMABRD), Secured Ant Colony Optimization (SACOP) and Fingerprint based Zero Knowledge Authentication (FZKA) is applied to a real time environment. While comparing three algorithms, SACOP has higher detection probability of malicious nodes at the expense of increased storage and communication overheads over EMABRD and FZKA. FZKA performs better compared to EMABRD in terms of detection probability but at the cost of increased overheads. So, among the three algorithms, EMABRD is better in terms of overheads and SACOP is better in terms of detection probability.